IMPLEMENTASI MEDIA GAME EDUKATIF "JELAJAH NUSANTARA" DALAM PEMBELAJARAN PKN UNTUK MENINGKATKAN KESADARAN KEBERAGAMAN BUDAYA SEBAGAI PEMERSATU BANGSA - Abida Ferindistika Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The low level of student awareness regarding cultural diversity in Civic Education (PKn) classes is one of the most common issues in education in Indonesia. Currently, the reliance on one-way teaching methods prevents students from actively engaging in the learning process, resulting in the incomplete internalization of the values of diversity. Therefore, this study aims to: (1) describe how the educational game “Jelajah Nusantara” is implemented in the PKn curriculum; (2) analyze the increase in students’ awareness of cultural diversity following the implementation of this educational game; and (3) examine whether there is an increase in students’ learning engagement during the learning process. The method applied in this study was Classroom Action Research (CAR) using the Kemmis and McTaggart model, implemented over two cycles. The research subjects consisted of 30 eighth-grade students from Class VIII B at SMPN 4 in Madiun City during the even semester of the 2025/2026 academic year. Data were collected through questionnaires, observations, and documentation. The results of the study showed a significant increase in students’ cultural awareness scores from Cycle I to Cycle II, as evidenced by the achievement of success indicators, with a class-wide mastery rate exceeding 75%. Based on these findings, it is evident that the integration of educational games based on cultural exploration is capable of creating meaningful learning experiences for students and can foster an attitude of tolerance toward diversity as the primary foundation for national unity.